Relevance Of Angiotensin Converting Enzyme Gene Polymorphism 1978124 With Hypertension In Type 2 Diabetes Mellitus - Shaimaa Addai Hummady; Abdul Hussein Alwan Algenabi (مجلة الكوفة الطبية)
Background: Cardio vascular disease is public in diabetes. Angiotensin-converting enzyme (ACE)2 is a recently described member of the RAS, and this study examined ACE2 polymorphism is associated with hypertension and in Type 2 diabetes mellitus (T2DM).it was linked to enlarged chances hypertension was significant peripheral vascular issues, including both macro- and micro-vascular complications. Aim of study: To evaluate the risk of ACE2 gene polymorphism (rs1978124) in the development of Hypertension also to estimate the ACE2 levels in the recruited individuals. Method: the study is case control from September 2023 Variant ACE2 (rs1978124) examined in 200 Iraqi subjects diabetic. 90 hypertensive diabetic patients (case group) and 110 normotensive diabetic patients (control group) were included. Patients age>30 years old. diagnosed by physicians having T2DMwith and without Hypertension. Polymerase chain reaction (PCR) used to detect the A/G alleles. Results: The results for rs1978124 in HT diabetic patients with, as well as in NT diabetic control were analyzed after adjusting for age, sex, and BMI was no statistically significant in all hereditary models and the minor allele frequency analysis, showed no significant differences. Conclusion: ACE2 gene polymorphism rs1978124 is non linked to the hypertension in T2DM Iraqi peoples